Employee empowerment and its performance in emerging economy: mediating role of psychological capital - Sayem, S.M.; Akter, Most. Sadia; Islam , Md Muktadir; Islam, Azharul (Serbian Journal of Management, 2025)
The study aims to examine the mediating role of psychological capital between employee empowerment and its performance in an emerging economy like Bangladesh. A structured questionnaire has been distributed among employees serving in different public and private organizations in Bangladesh. Data collected from 385 respondents are analyzed with Partial Least Square Structural Equation Modeling (PLS-SEM) to test hypothetical relationships among the latent constructs. The results showed that both structural and psychological empowerment positively influence employee performance. The psychological capital which presents a significant positive influence on performance, also mediates the positive relationship between both empowerment (structural and psychological) and employee performance.  The study pioneered in establishing psychological capital as a mediator between empowerment and employee performance in a developing economy context like Bangladesh. The results would provide valuable insights for the organization in designing human resource policies and training programs that will empower employees which leads to improved psychological capital and subsequently enhance their performance.
Keywords: employee empowerment; structural empowerment; psychological empowerment; psychological capital; employee performance